Formation of sustainable competitive advantages in the development of a construction company strategy based on value innovation - Vyacheslav Aleksandrovich Vlasenko (Недвижимость: экономика, управление, 2023)
The current situation, characterized in risk management as “external shocks”, leads to the need to adapt the strategy of enterprises to focus on the formation of sustainable innovative competitive advantages that create opportunities for technological breakthrough. The Russian economy still has a low level of innovation activity, high dependence on imported technologies in the most important sectors of the economy, including construction, a number of government programmes promoting innovation have not yielded the expected results. Changing this situation requires new approaches, including the identification of trends in the formation of innovative values. This task is particularly relevant for enterprises in the construction industry, designed to become a driver of economic development in accordance with industry strategic guidelines. The need to increase the competitiveness of Russian construction enterprises in conditions of economic instability and external shocks, which entails the search for possible ways to form and retain competitive advantages. The practical significance of this study lies in the argumentation of sources and methods of formation of sustainable competitive advantages, the key of which is innovation, from the position of value-oriented approach. The application of value innovation, as a source of sustainable competitive advantages has led to the growth of the main indicators of enterprise development. The article presents a methodological toolkit, which consists of the procedure and strategy for the formation of value innovation, as well as the scheme of “six ways” of value innovation, forming sustainable competitive advantages in the development of the strategy of the construction enterprise based on value innovation, implemented on the example of a large infrastructure construction enterprise JSC “RZDstroy”.